Necesidades de la vida en la muerte - Combinato, Denise Stefanoni; Martin, Sueli Terezinha Ferrero [UNESP] (FapUNIFESP (SciELO), 2017)
Due to the aging of the population and the increase in Non transmissible chronic diseases, the Family Health Strategy (ESF) is progressively facing the needs of people undergoing the dying process. By analyzing the work of health practitioners taking care of people who are dying, the aim of this paper is to discuss health needs through this process, in order to give support to those who work in this area in Primary Health Care. Eleven nurses and physicians linked to the ESF in Campinas, SP were selected for the interview after answering two questionnaires. Data analysis followed the theoretical and methodological framework of the historical-cultural Psychology. Results show that patients and families’ needs are not restricted to the particular life moment of the proximity to death, but also are related to social vulnerability conditions.
Necessidades da vida na morte
Vital needs in the dying process
Keywords: Historical-cultural psychology; Palliative care; Primary health care